Peace, Jihad & Conflict Resolution (American Journal of Islam and Society, 2003)
The international seminar on Peace, Jihad & Conflict Resolution, jointlyorganized by AMSS, IIIT, and the Islamic Educational, Scientific andCultural Organization (ISESCO), was hosted by the Center for Muslim-Christian Understanding (CMCU), Georgetown University on November 2-3, 2002. The seminar’s goal was to bring a deeper understanding of the place andposition of religion in general, and Islam in particular, toward the dynamicconcepts of peace, jihad, political violence, and military conflict. The seminargot off to a lively start on Saturday morning with introductions presentedby Dr. Jamal Barzinji (vice president, IIIT). Welcoming remarks weremade by Dr. Ahmad S. Weld Abah (chairman, ISESCO Executive Council),Dr. Louay Safi (AMSS president), and Dr. John Esposito (CMCU director).The opening session was followed by an inspiring speech by Dr. Taha Jaberal-Alwani (president, Graduate School of Islamic and Social Sciences[GSISS]), on “Concepts between Islamic and Western Worldviews: Jihad asan Example.”Al-Alwani analyzed the meaning of peace, jihad, and conflict resolutionfrom an Islamic jurisprudential perspective by examining how these conceptsare governed by the values of tawhid (unity of God), tazkiah (purificationof humanity), and ‘imran (establishing a values-based civilization).He discussed how practicing and establishing peace is obligatory for all people,because Islam considers humanity to be one family. Since most ofIslam’s jurisprudential rules are based on peace, according to al-Alwani,“both peace and jihad have different levels, and each one should be fulfilledby individuals, family, and society.” He characterized jihad as: “There is noother concept that will match the meaning of peace in Islam except jihad,”and argued that “jihad is based on different levels: to struggle is the majormeaning of jihad, in order to elevate oneself to a higher level, they muststrive.” The concept of conflict resolution implies that many stages shouldbe applied and negotiated before resorting to war.Thirty-two papers were presented in eight consecutive panels duringthe 2-day seminar. The panelists approached the issues from theoretical perspectivesand sociopolitical experiences in order to overcome stereotypicaldiscussions and superficial impressions. On the first day, the following subthemeswere analyzed in four panels: “Jihad, War and Peace in the IslamicAuthoritative Texts,” “Positive Attitude toward the ‘Other’,” “Religion: ATool for Conflict Resolution,” and “Religious and Cultural Roots of Warand Peace.”These panels drew attention to the need of developing an authenticmethodology that deals objectively with religious texts and history. In thefirst panel, Dr. Jamal Badawi (St. Mary’s University, Canada) offered a newvision in his analysis of how some misunderstood verses and ahadith haveleft a negative impact upon the nature of Muslim and non-Muslim relations.He addressed such questions as: “Does Islam teach hate toward others?” ...